Inherited or Immunological Thrombocytopenia: The Complex Nature of Platelet Disorders in 22q11.2 Deletion Syndrome - Urbański, Bartosz; Urbańska, Zuzanna; Bąbol-Pokora, Katarzyna; Subocz, Ewelina; Młynarski, Wojciech; Janczar, Szymon (Seminars in Thrombosis and Hemostasis, 2025)
22q11.2 deletion syndrome (22q11.2DS) is one of the most common congenital malformation syndromes resulting from disrupted embryonic development of pharyngeal pouches. The classical triad of symptoms described by Angelo DiGeorge is frequently accompanied by hematological and immune disorders. While it is well-established that patients with 22q11.2DS have an increased risk of recurrent autoimmune cytopenias, including immune thrombocytopenia, the platelet abnormalities in this population are more complex and multifaceted. Given this issue, we conducted a comprehensive literature review on platelet disorders in 22q11.2DS using accessible databases (PubMed and Scopus). We aimed to outline previous studies limitations and most urgent challenges concerning thrombocytopenia in these patients. One characteristic finding frequently observed in 22q11.2DS is mild macrothrombocytopenia caused presumably by the loss of one GP1BB allele, encoding the element of the GPIb–IX–V complex. This structure plays a central role in thrombocyte adhesion, aggregation, and subsequent activation. Recent studies suggest that defective megakaryopoiesis and impaired vasculogenesis may strongly influence platelet and hemostasis disorders in 22q11.2DS. Furthermore, the phenotypic manifestation may be modulated by epigenetic factors and gene expression modifiers located outside the deletion region. Although the final hemorrhagic phenotype is typically mild, these patients may require more frequent transfusions following major surgical procedures. Despite the risk of thrombocytopenia and thrombocytopathy, there is a lack of large-scale research on hematological anomalies in 22q11.2DS, and the available results are often inconclusive. Given the complexity of hemostatic disorders, it is essential to establish specific recommendations for perioperative management and autoimmune cytopenias treatment within this population.
Keywords: 22q11.2 deletion syndrome; DiGeorge syndrome; inherited thrombocytopenia; immune thrombocytopenia; Bernard–Soulier syndrome